Do morphologic characteristics play a role in nodal metastatic progression of well-differentiated pancreatic neuroendocrine tumors?. Issue 1 (February 2021) - Ugras, Nesrin; Hasdemir, Seçil; Yerci, Ömer; Taşar, Pınar; Dündar, Halit Ziya; Macunluoğlu, Aslı Ceren
Background: Pancreatic neuroendocrine neoplasms (NENs) are tumors with histopathologic and prognostic heterogeneity that pose difficulties in establishing standards for diagnosis, classification, and treatment. Among NENs, well-differentiated neuroendocrine tumors (NETs) have been classified as grade 1, 2, and 3 in the most recently released World Health Organization classification. Although well-differentiated NETs are associated with relatively better prognosis, they have a potential for malignant behavior such as extrapancreatic spread, metastasis, or recurrence. The present study aimed to evaluate clinical and histomorphologic findings of patients with well-differentiated pancreatic NETs and to identify histopathologic findings effective in predicting nodal metastatic progression. Methods: The study group consisted of 54 patients diagnosed with well-differentiated NET. All preparations and blocks of the patients were examined for the following histopathologic parameters: tumor diameter, microscopic tumor growth pattern (solid, trabecular, acinar, and mixed), cellular features (clear, eosinophilic, oncocytic, peliotic, and pseudopapillary), stromal changes (calcification, lymphocytic infiltration, and stromal hyalinization), presence of necrosis, perineural invasion, lymphovascular invasion, mitotic activity, and Ki67 proliferative index. Results: Lymph node metastasis was present in 7 patients. Lymph node metastasis was significantly associated with tumor diameter of >2 cm ( p = 0.012), Ki67 proliferative index of >20% ( p = 0.022), grade 3 tumors ( p = 0.002), presence of dense stromal hyalinization ( p = 0.034), and mild lymphocytic infiltration ( p = 0.041). Conclusion: The present study revealed that the new findings such as presence of dense stromal hyalinization and absence of remarkable lymphocytic infiltration could be predictive morphologic findings for the development of lymph node metastasis.